A man in search of God. Christian paradigm in the poems of Mirko Jirsak - Rękas, Joanna (Slavia Occidentalis, 2014)
The primary objective of the study is to find and decode the reconstruction of the Christian paradigm in the poems of Mirko Jirsak (1909–1999), a Croatian poet, writer, journalist and translator. In the search of the model of the works, I prioritise marking the human hiding behind the lines, i.e. the poetic consciousness, which is expressed in the works. The poet’s anthropology is based on the essential status of man, the aim of his earthly existence, origin and place of residence (anthropology of the image and of similarity). The key for the definition of Jirsak’s man is hidden in the Christian marking of a person as a secret.